1990
DOI: 10.3109/00048679009077703
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Dementia Carers: Doctors' Communications, Problem Behaviours and Institutional Care

Abstract: A survey of carers belonging to the Alzheimer's Disease and Related Disorders Society (ADARDS) had three aims: (i) to investigate the process of health professionals providing information to patients and carers: (ii) to determine the nature of problems burdening carers; and (iii) to examine factors associated with institutional placement. Carers reported on deficiencies in the provision of information and indicated their preferences as to how the information should be given. ADARDS, general practitioners and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…This confirms the finding of Gély-Nargeot et al (2003) that 36.8% of carers were not satisfied with the information provided at diagnosis. Further, in a survey of carers by Brodaty et al (1990) fewer than half of carers recalled being given information about management and prognosis during diagnosis. The current survey revealed that details regarding drug treatments and dementia were poor, with one-fifth of carers receiving no information at this stage, and less than half of respondents reportedly satisfied with the information supplied at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms the finding of Gély-Nargeot et al (2003) that 36.8% of carers were not satisfied with the information provided at diagnosis. Further, in a survey of carers by Brodaty et al (1990) fewer than half of carers recalled being given information about management and prognosis during diagnosis. The current survey revealed that details regarding drug treatments and dementia were poor, with one-fifth of carers receiving no information at this stage, and less than half of respondents reportedly satisfied with the information supplied at diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, home assistance could be offered in order to reduce the caregiver burden. It has been suggested that caregivers play an important role in decision making regarding patient care, for example regarding medication use [33,34] , yet attrition prevention strategies have generally not been targeted towards caregivers [35] . It is important to convince the caregiver of the importance of regular medical care and attention for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…It is doubtful whether openness in relaying a diagnosis to patients has been achieved as common practice, although relatives and carers are more likely to be told the truth (Brodaty et al, 1990;Rice & Warner, 1994). However, without clear, shared communication to both patients and carers together, this may cause difficulties within families, members being unable to confide and share distress, and harbouring guilt and shame.…”
Section: 'Truth-telling' and Dementiamentioning
confidence: 95%
“…The first comprehensive study in the literature to examine views of dementia carers was carried out in Australia (Brodaty et al, 1990). A questionnaire was sent to members of a national carers' organisation.…”
Section: What Do Carers Want?mentioning
confidence: 99%